Biopsychosocial Factors Associated with the Risk of Hypertension in Elderly in Klaten, Central Java: A Cross-Sectional Study - Indri Nur Utami; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, 2024)
Background: Hypertension is also a major preventable risk factor for cardiovascular disease, and plays a role in all causes of death worldwide, characterized by systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg. The purpose of this study was to analyze the effect of biopsychosocial factors on the risk of hypertension among the elderly in Klaten Regency.Subjects and Method: This study was cross-sectional from April-May 2024. The sample used was 200 elderly people in 25 elderly health posts and selected using random sampling techniques in Klaten Regency, Central Java. The dependent variable of this study was the incidence of hypertension. The independent variables of this study were age, gender, anxiety, stress, and income level. The data were collected using questionnaire and analyzed using path analysis run on Stata 13.Results: Systolic blood pressure is directly affected by anxiety (b= 1.34; CI 95%= -0.13 to 2.82; p= 0.075), the existence of retirement funds (b= -0.09; CI 95%= -0.01 to -0.03; p= 0.003), and female (b= 1.22; CI 95%= -5.38 to 7.84; p= 0.716). Anxiety is influenced by stress (b= 0.38; CI 95%= 0.29 to 0.48; p<0.001), the existence of retirement funds (b= -0.01; CI 95% <0.01 to <0.01; p= 0.038), and age (b= 0.04; CI 95%= 0.07 to 0.08; p= 0.020).Conclusion: Systolic blood pressure is directly affected by anxiety, the existence of retirement funds, and female. Anxiety is influenced by stress, the existence of retirement funds, and age.